Mechanisms for the modification of nylon 6, 12 by gamma irradiation. (1st January 2003) - Menchaca, C.; Alvarez-Castillo, A.; Martinez-Barrera, G.; Lopez-Valdivia, H.; Carrasco, H.; Castano, V. M.
Polyamide 6, 12 crystalline fibers, commercially known as Nylon 6, 12, were irradiated using gamma radiation and characterised by Infrared Spectroscopy (FT-IR), Raman, Differential Scanning Calorimeter (DSC) and Thermogravimetric Analysis (TGA). The analysis of the data, by using Flory's Theory and the principles of the Compton effect, allowed establishment of a reaction mechanism to explain how the polyamide chains are modified.